Dissociation of Cyclopropanone Molecule and Ion (Journal of Atomic and Molecular Sciences, 2014)
Investigate the dissociation and ionization process of cyclopropanone moleculesby using the Density functional method. Find the transition states of cyclopropanonemolecule and ion, and get the products from transition state to isomer. At the same time, calculate frequency and energy. Confirm their transition states betweenthe reactants and resultants through the Intrinsic Reaction Coordinates (IRC)calculation.